Exploration of essential oil from Psychotria poeppigiana as an anti-hyperalgesic and anti-acetylcholinesterase agent: Chemical composition, biological activity and molecular docking. (5th October 2022) - Formagio, Anelise Samara Nazari; Vilegas, Wagner; Volobuff, Carla Roberta Ferreira; kassuya, Candida Aparecida Leite; Cardoso, Claudia Andrea Lima; Pereira, Zefa Valdevina; Silva, Rosilda Mara Mussury Franco; dos Santos Yamazaki, Diego Alberto; de Freitas Gauze, Gisele; Manfron, Jane; Marangoni, Janaine Alberto
Abstract: Ethnopharmacological relevance: Leaves from Psychotria poeppigiana Müll. Arg. (accepted as Palicourea tomentosa (Aubl.) Borhidi), Rubiaceae, has traditionally been used in medicine for treatments of inflammation and pain; Synonymously, Cephaelis elata for the treatment of dementia; However, few scientific studies have been evidence demonstrating this activity. Aim of the study: The aim of this study was to investigate the chemical composition of P. poeppigiana essential oil obtained from leaves (EOPP) and its antioxidant, anti-inflammatory and acetylcholinesterase (AChE) activities. Molecular docking simulations were carried out with the main constituents. Materials and methods: EOPP (hydrodistillation) was analysed by gas chromatography-mass spectrometry (GC–MS). The fractionation of EOPP afforded germacrene D and bicyclogermacrene. The antioxidant activity of EOPP was determined by MDA assay. The inflammatory parameters were evaluated using CFA model (with paw edema, mechanical, thermal hyperalgesia, MPO and NAG) in EOPP (30, 100 and 300 mg/kg), germacrene D and bicyclogermacrene (30 mg/kg). The AChE inhibition was evaluated in rat brain structures and molecular docking simulations were carried out using Autodock v.4.3.2. Results: GC-MS analysis identified 19 compounds, and the major compounds were germacrene D (29.38%) and bicyclogermacrene (25.21%). EOPP exhibited high antioxidant capacity (IC50  = 12.78 ± 1.36 μg/mL). All the tested doses of EOPP and both major constituents significantly inhibited cold and mechanical hyperalgesia and significantly blocked the increase in MPO activity 24 h after the CFA injection. There was significant AChE inhibition by EOPP and germacrene D in the cerebral cortex and hippocampus (>50%). Enzyme-ligand molecular modelling showed that the major constituents of EOPP interacted differently with AChE. Conclusions: The chemical compounds of the essential oil from the leaves of P. poeppigiana is based mainly on terpenes, the sesquiterpenes germacrene D (29.38%) and bicyclogermacrene (25.21%) being the major compounds. EOPP presented antioxidant, anti-inflammatory and anti-acetylcholinesterase (AChE) activities. Besides, enzyme-ligand molecular modelling showed the EOPP may act as an anti-hyperalgesic and AChE inhibitory agent. Taken together, these results might be in accordance with if folk use for pain- and inflammation-related symptoms. Graphical abstract: Image 1